Problematika Uang Panai Dalam Pernikahan Masyarakat Suku Bugis Bone - Rinaldi Rinaldi; Fatimah Azis; Jamalauddin Arifin (Universitas Lambung Mangkurat, 2023)
This article aims to understand the problems of panai money in the marriage of the Bugis Bone community. This research uses a case study method with a qualitative approach. The data collection technique is through interviews, observation, and documentation studies. The data is then analyzed by looking at the problems that arise from the large demand for panai money from women's families. The results showed that: 1). The problem with the high demand for panai money is a big problem that deviates from the siri culture, for example elopement (silariang), pregnancy out of wedlock, old virgins and sometimes panai money is used as a form of rejection to the men by setting a high panai money so that the men unable to fulfill the request. 2). Strategies for anticipating and solving the problem of banknotes.